Non-linear recurrent analysis of the behavior of a complex technological object - Kyshenko, Vasil; Ladanyuk, Anatoly; Sych, Maryna; Shkolna, Olena (My University, 2016)
For the efficient management of a technological complex of a sugar plant, based on the synthesis of synergetic managing strategies, it is necessary to perform a number of experimental studied by methods of nonlinear dynamics. The applied method is built on such a property of a complex system as recurrence. This method of analysis is based on the representation of the properties of a complex object of management in the form of geometric space-time structures and their quantitative assessments. It, accordingly, makes it possible to carry out a prompt analysis of its behavior for making resource saving management decisions. When creating information management systems of complex objects there is always a task of assessing their state. This is caused by a continuous change in both the external environment and the object’s parameters, which is relevant for a technological complex of a sugar plant. It was established that the character of the processes that occur in the technological complex of a sugar plant is predetermined by the intermittency in behavior while it is also subject to laws of the theory of dynamic chaos. Chaotic behavior of technological objects was explored by the methods of nonlinear dynamics, which allowed us to determine qualitative and quantitative assessment of deterministic chaos. This, in its turn, makes it possible to develop of efficient systems of synergetic management that ensure maximal use of own resources of the object of management owing to the phenomena of self-organization. Для ефективного керування технологічним комплексом цукрового заводу на основі синте- зу синергетичних керуючих стратегій необхід- но встановити наявність явищ самоорганізації. Рекурентний аналіз проводився на представлен- ні властивостей складного об'єкта керування у вигляді геометричних просторово-часових струк- тур. Визначені кількісні оцінки детермінованості, стохастичності та хаотичності в поведінці технологічних процесів цукрового виробництва дозволили організувати ресурсоощадні керуючі дії.
Keywords: recurrent plots; time series; sugar plant; synergetic management; nonlinear dynamics; рекурентна діаграма; часовий ряд; цукровий завод; синергетичне керування; нелінійна динаміка; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка